153k views
1 vote
25 POINTS ANSWER FAST!

25 POINTS ANSWER FAST!-example-1

2 Answers

3 votes

Answer:

5x(2x + 1) - 3(2x + 1) = 0

<=> (5x - 3)(2x + 1) = 0 => Option 1 is true.

<=> 5x - 3 = 0 or 2x + 1 = 0

<=> 5x = 3 or 2x = -1

<=> x = 3/5 or x = -1/2

=> Option 2 is false.

=> Option 3 is true.

Hope this helps!

:)

User Ruchi
by
5.7k points
1 vote

First one is true , because by grouping method , it is justified.

Second one is false , because by putting 5x- 3 and 2x+1 = 0 , we get solutions 3/5 and -1/2 not 1/2

Third is true as I told above 3/5 is one of the zero.

I hope this all helps you : )

User Phillip Trelford
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.